VD_FINDINFO HC / 2009 / 14 vom 8. April 2009 - VD Tribunal cantonal (2009)
PAR MÉTIER, FIXATION DE LA PEINE, PEINE COMPLÉMENTAIRE, SURSIS À L'EXÉCUTION DE LA PEINE | 139 ch. 2 CP, 42 CP, 47 CP, 49 CP, 415 CPP